Isolation and Analysis of Microplastics in Ikan Tongkol Euthynnus affinis Cantor, 1849 at Tanjung Luar Fish Landing Base, East Lombok - Syahadatina, Rifqah Hashifah; Prasedya, Eka Sunarwidhi; Candri, Dining Aidil (Jurnal Biologi Tropis, 2024)
The increasing amount of plastic consumption in Indonesia has an impact on the accumulation of plastic waste on land as well as water, with the nature of plastic that is difficult to decompose by microorganisms causing many organisms to be polluted by the waste. Therefore, research on microplastic content needs to be done to determine the safety of fish which is the food of the community. This study was conducted to find out how the abundance of microplastics as well as the characteristics of microplastics contained in Ikan Tongkol  (Euthynnus affinis) at PPI Tanjung Luar, through an isolation process using a 10% KOH solution added to fish meat, then incubated until both were homogeneous in a water bath at 70°C, 150 rpm. Furthermore, the homogenized sample was filtered using a 250 µm graded sieve. After filtering the sample will be put into a dryer at 40°C for 2 hours before being observed under a microscope. The results of this study indicate that microplastics have accumulated in fish with an abundance of 8.6 MP/Ind with the type of microplastics that most accumulates in the meat of Tuna (Euthynnus affinis) is fiber type microplastics as much as 81% of the total sample and the most dominant color is black. There are 4 microplastics found accumulated in the meat of Euthinnus affinis, namely 81% fiber, 11% fragments, 6% film, and 2% granules.